1999
DOI: 10.1016/s0893-133x(99)00042-1
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1B Receptors: A Novel Target for Lithium Possible Involvement in Mood Disorders

Abstract: Lithium ion is widely used to treat depressive patients, often as an initial helper for antidepressant drugs or as a moodLithium is a simple monovalent cation that represents one of the most important compounds used in psychiatry. It is widely used and remains the most effective treatment for mania and for the prevention of recurrent episodes in both mania and depression (Schildkraut

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 44 publications
2
30
0
1
Order By: Relevance
“…It is interesting to note that several earlier studies reported that lithium selectively inhibited 5-HT binding to 5-HT1BR, reduced 5-HT1BR-induced GTP␥s binding, and abolished 5-HT1BR-reduced adenylyl cyclase activity (Massot et al, 1999). Similar results were observed in human platelets from both healthy and depressed subjects where lithium dose-dependently reversed the inhibitory effect of a 5-HT1BR agonist on adenylyl cyclase (Januel et al, 2002).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…It is interesting to note that several earlier studies reported that lithium selectively inhibited 5-HT binding to 5-HT1BR, reduced 5-HT1BR-induced GTP␥s binding, and abolished 5-HT1BR-reduced adenylyl cyclase activity (Massot et al, 1999). Similar results were observed in human platelets from both healthy and depressed subjects where lithium dose-dependently reversed the inhibitory effect of a 5-HT1BR agonist on adenylyl cyclase (Januel et al, 2002).…”
supporting
confidence: 76%
“…It is interesting that several early investigations observed that lithium had a noticeable effect on 5-HT1BR (Massot et al, 1999), but the mechanism of this action was not revealed. In this study, we used several experimental approaches to determine whether GSK3 has an impact in agonist-induced activation of 5-HT1Rs and whether subtypes of 5-HT1Rs are differentially regulated by GSK3.…”
mentioning
confidence: 99%
“…Chronic lithium is reported to increase the 5-HT concentration in the serotonergic synaptic cleft by reducing 5-HT 1 density, particularly the density of presynaptic 5-HT 1B receptors, but it does not appear to affect 5-HT 2A/ 2C receptor density (Friedman and Wang, 1988;Goodwin, 1989;Haddjeri et al, 2000;Januel et al, 2002;Massot et al, 1999;Mizuta and Segawa, 1988;Redrobe and Bourin, 1999). As 5-HT 1B receptors depress presynaptic 5-HT release, lithium's elevation of k* for AA in auditory and visual areas may result from derepressed 5-HT release, elevated 5-HT in the cleft, or an increased 5-HT 2A/2C -mediated activation of PLA 2 (Januel et al, 2002;Redrobe and Bourin, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in nuclear charge per unit volume indicated that nuclear strength of Li + ions in treated lithium powder probably increased after biofield treatment. It is reported that Li + plays an important role in central nervous system in releasing the serotonin from neurons [5,27,28]. Thus, it is assumed that serotonin releasing activity of Li + in treated sample may be higher as compared to control.…”
Section: Thermogravimetric Analysis-differential Thermal Analysis (Tgmentioning
confidence: 99%
“…In addition, it is widely spread in central nervous system and interacts with many neurotransmitters and receptors, thus increasing serotonin synthesis [4]. Further, it is also reported that lithium ions (Li + ) can increase the release of serotonin or 5-hydroxy tryptamine by neurons in the brain [5]. Furthermore, the most commonly prescribed lithium salts include lithium carbonate (Li 2 CO 3 ), lithium orotate (C 5 H 3 LiN 2 O 4 ), and lithium citrate (Li 3 C 6 H 5 O 7 ) for pharmacological treatment in mentally disordered patients [6,7].…”
Section: Introductionmentioning
confidence: 99%